A philosophical approach to the concept of handedness: The phenomenology of lived experience in left- and right-handers. Issue 2 (4th March 2017) - Westmoreland, Peter
ABSTRACT: This paper provides a philosophical evaluation of the concept of handedness prevalent but largely unspoken in the scientific literature. This literature defines handedness as the preference or ability to use one hand rather than the other across a range of common activities. Using the philosophical discipline of phenomenology, I articulate and critique this conceptualization of handedness. Phenomenology shows defining a concept of handedness by focusing on hand use leads to a right hand biased concept. I argue further that a phenomenological model based in spatial orientation rather than hand use provides a more inclusive concept of handedness.